An answer to an important controversy and the need for caution when using simple models to predict inelastic earthquake response of buildings with torsion. - Anagnostopoulos, Stavros A.
This paper presents evidence that the extension of conclusions based on the widely used simplified, one story, eccentric systems of the shear-beam type, to actual, nonsymmetric buildings and consequent assessments of the pertinent code provisions, can be quite erroneous, unless special care is taken to match the basic properties of the simplified models to those of the real buildings. The evidence comes from comparisons of results obtained using three variants of simplified models, with results from the inelastic dynamic response of three and five story eccentric buildings computed with detailed MDOF systems, where the members are idealized with the well-known plastic hinge model. In addition, a convincing answer is provided on a pertinent hanging controversy : For frame type buildings, designed in accordance with the dynamic provisions of modern codes (such as EC8 or IBC2000), which allow reduced shears at the stiff edge due to torsion, the frames at the flexible sides are the critical elements in terms of ductility demands.
Keywords: Earthquake; Torsion; Nonlinear seismic response; Simplified models; Multistorey buildings